Rational mucolytic therapy with ambroxol: controversial and indisputable. A review - Sergey L. Babak; Marina V. Gorbunova; Andrey G. Malyavin (ZAO "Consilium Medicum", 2023)
Many years of experience in the use of ambroxol is based on its ability to regulate the basic mechanisms of physiological production and transport of bronchial mucus. The main indication for ambroxol is the mucolytic therapy of acute and chronic bronchopulmonary diseases associated with hypersecretion and impaired mucus transport. Ambroxol has a number of the following properties: high secretolytic activity (promotes mucus clearance, facilitates expectoration of sputum, reduces productive cough); anti-inflammatory and antioxidant activity; local analgesic (anesthetic) effect through the blockade of sodium channels of cell membranes. The effect of anesthesia of the mucous membranes is attributed to the new pharmacological action of ambroxol, useful in the treatment of acute respiratory tract infections. The efficacy and safety of ambroxol in clinical practice has been confirmed by half a century of experience in its administration. The purpose of this publication was an up-to-date assessment of the controversial and indisputable chemical, pharmacological, clinical data on the properties of ambroxol in the concept of modern recovery mucolytic therapy that can improve the therapy and prognosis of patients with tracheobronchial secretion hypersecretion, impaired mucociliary clearance and unproductive cough.